Relationship between State and Civil Society: Theoretical Review - Abdou Barrow (Indonesian Journal of Sociology, Education, and Development, 2020)
Relationship between state and civil society has been of great interest in the field of social sciences especially in the field of sociology and political science. There have been several theorist that tries to look into this relationship. The aim of this paper is to review the theoretical approaches of Marxist, Elites, and Neo-Consensualist on the relations between state and civil society in nowadays societies. Research are based on literature studies, on conflict perspectives in sociology. These theories are very prominent when talking about state-civil society relationship in sociology. Marxist looks the relationship between the two as conflictual, meaning dominant civil society use the state as an instrument in exploiting the weak economic class. Elites argue the relationship differently from that of Marxist and liberals, as for them, state is run by few individuals at the expense of the mass. In the eye of Neo-Consensualist is entirely a different story, as that of Parson view certain prospectin the social world of constituting the society that is; norms, and values. As for Bellah he sought religion as a mechanism in the spirit of acculturating a kind of doctrine in a sense that, state and citizens go bye. Result for this theoretical views is elites show the relationship different from the Marxist and liberals, as for them the state is run by few individuals at the expense of the mass. This people are a minority group that has influence through economically, socially and the like but in short they have potentials in making things happen. This minority group the called them the elite as the mas they called the ruled.